2017
DOI: 10.1371/journal.pone.0181305
|View full text |Cite
|
Sign up to set email alerts
|

Generalized structural equations improve sexual-selection analyses

Abstract: Sexual selection is an intense evolutionary force, which operates through competition for the access to breeding resources. There are many cases where male copulatory success is highly asymmetric, and few males are able to sire most females. Two main hypotheses were proposed to explain this asymmetry: “female choice” and “male dominance”. The literature reports contrasting results. This variability may reflect actual differences among studied populations, but it may also be generated by methodological differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
0
22
0
1
Order By: Relevance
“…Therefore, the model and proposed hypotheses were tested using generalised multilevel structural equation modeling (GSEM) with STATA. GSEM is a technique that combines the flexibility and power of both Generalized Linear Models and Structural Equation Models in an integrated modeling framework (Lombardi et al 2017). It simultaneously considers direct and indirect effects of several interacting factors and is ideal for addressing hypotheses with nested data (Preacher et al 2010;Lombardi et al 2017).…”
Section: Analytic Strategymentioning
confidence: 99%
“…Therefore, the model and proposed hypotheses were tested using generalised multilevel structural equation modeling (GSEM) with STATA. GSEM is a technique that combines the flexibility and power of both Generalized Linear Models and Structural Equation Models in an integrated modeling framework (Lombardi et al 2017). It simultaneously considers direct and indirect effects of several interacting factors and is ideal for addressing hypotheses with nested data (Preacher et al 2010;Lombardi et al 2017).…”
Section: Analytic Strategymentioning
confidence: 99%
“…However, because a negative agreement was not considered, the Rasch positive probability did not measure the probability of revealing truth from a PROM. Our approach is related to latent variable models for similar problems [ 37 , 38 ] in the sense that a iz can be regarded as a latent variable. On the other hand, we do not assume a particular distribution for a iz , which makes our approach different from most latent variable models.…”
Section: Methodsmentioning
confidence: 99%
“…However, GSEM estimations using the Stata software are unable to compute goodness-of-fit indices. To address this issue, we performed case-specific residual examinations based on the principle that the residuals should have a mean 0 if the observed and predicted frequencies match well [37]. We found that residuals had a mean very close to 0; this suggests that our model was high-quality and fitted well with the data.…”
Section: (Table 1)mentioning
confidence: 97%